Shazam! [videorecording (DVD)] - Sandberg, David F., 1981-; Levi, Zachary, 1980-; Strong, Mark, 1963-; Angel, Asher (Warner Bros. Entertainment, 2019)
A foster child discovers that he has the ability to transform into the grown up superhero, Shazam.